Rapid solution exchange to entire neuronal cultures grown on multi electrode arrays - Herzog, Nitzan (2017)
Volume transmission in the brain is a communication modality mediated by diffusion of signalling species in the extrasynaptic space. This mode of communication is thought to be significantly involved in cognitive processing but nevertheless remains poorly understood and its study has been hampered by the lack of experimental tools for faithfully recreating the spatiotemporal patterns of these processes in a controlled manner. Microfluidics technology, which allows rapid and precise manipulation of fluid at the micron scale is ideally suited for generation of precise spatiotemporal patterns of chemical species. Past microfluidics work applied to neuroscience has mainly focused on generating slow spatial gradients but have not accounted for signals occurring in rapid time scales such as in the neuromodulatory systems where agonist pulses lasting just a few seconds are generated. Producing such rapid signals using microfluidic technology requires rapid flow rates which is challenging, not just in terms of the liquid handling, but also with respect to the biology and well-being of the neurons when subjected to such flow. This thesis describes the development of a microfluidic system for mimicking rapid volume transmission processes by producing rapid agonist transients to a neuronal microculture while preserving the electrophysiological properties of the cells.